Treatment of Landfill Leachate using Cockle Shell as an Alternative Adsorbent for the Removal of Ammonia Nitrogen and COD. Issue 1 (December 2020) - Yahaya, Izat; Daud, Zawawi; Fauzi, Basirah
Abstract: Adsorption system proved to be an effective method widely used in the treatment of wastewater in many studies. Despite that, most studies on the adsorption in wastewater treatment, focused more on the removal of organic and inorganic substances. The potential of cockle shell (CS) and zeolite (ZEO) as an absorbent has been investigated to obtain the optimum mixing ratio in removing two working parameters such as ammonia nitrogen (NH3 -N) and COD. Both CS and ZEO we mixed together in different ratio. The absorption batch study includes the preparation of 5g composite adsorbent, 200 mL of raw leachate sample at pH 8.64, with a shaking speed of 200 rpm for 300 minutes at room temperature. The result shows, the optimum ratio obtained for composite mixture absorbent is (3.5:0.5) and the concentration achieved for the ratio was 415 mg/L NH3 -N and 440 mg/L COD. The optimum contact time and absorbent size expressed the result at 300 minute and 1.18 mm with the percentage optimum removal value is 42.46% NH3 -N and 90.21% COD; and 50% NH3 -N and 85.14% COD, respectively during the experiment.